Socio-Economic Impact of Saving and Credit Cooperative: A Case of Janahitkari Saving and Credit Cooperative Surkhet - Yogi, Sagar Nath; Yogi, Sanjay (Karnali Outlook: Knowledge Across Disciplines, 2026)
Cooperatives have emerged as vital institutions for poverty alleviation and financial inclusion in Nepal, particularly in rural areas where agriculture remains subsistence-based and access to formal banking is limited. Savings and Credit Cooperatives bridge this gap by mobilizing savings, extending microcredit and providing skill-development opportunities. This study assesses the socio-economic impact of Janahitkari Saving and Credit Cooperative Limited in Birendranagar Municipality of Surkhet. A descriptive research design was applied using both primary and secondary data. Primary data was collected from randomly selected 368 members representing male and female equally. Data analysis employed simple statistical tools, such as number and percentage in tables. The results indicate significant economic and social improvements among cooperative members. Above three-fourths of the respondents reported increased income, while 81% improved their saving habits, reducing dependency on informal moneylenders. Social outcomes were also notable. Above four-fifths experienced enhanced social reputation, 78% gained new skills, and women, in particular, benefitted from greater decision-making power, leadership roles and financial independence. Similarly, 55% of the members secured new or improved livelihoods through cooperative-supported training. Despite these achievements, challenges persist. Around one-fourth of members failed to utilize loans productively, and landless individuals continued to face barriers due to collateral requirements. Training opportunities also remained unevenly distributed. Thus, the cooperatives are effective instruments for poverty reduction and empowerment in rural Nepal. However, reforms in inclusive lending, loan monitoring, and targeted youth- and women-focused programs are essential for maximizing their long-term developmental impact.